The aesthetic philosophy of Plato - Al-Taie, Hanan (Al-Adab Journal, 2025)
Plato has used one of the writing methods as a means of presenting his aesthetic ideas, the concepts of beauty and his aesthetic opinions. One of these writing styles which is known as dialogues was a means to present his ideas. The dialogue is characterized by its imaginative style; it does not explain the idea in a clear scientific way, rather, it explains it through metaphor, myths and stories. The Plato dialogue was the most successful method of expressing the truth; it tries to indicate to the truth, but it does not claim to comprehend it. It addresses only the elite of people who can perceive the truth and interpret it.